China-Pakistan Economic Corridor: China's Strategic Ambition - Septyanto Galan Prakoso; Andriyansyah Perdana Murtyantoro; Meisya Putri Intan Cahyani (JURNAL ILMU SOSIAL, 2019)
China’s Silk Road concept known as Belt and Road Initiative (B&R) by Xi Jinping aims at strengthening China’s economic power. One part of the initiative is the China-Pakistan Economic Corridor (CPEC). Using a qualitative descriptive method, we attempt to explain how China and Pakistan integrate themselves in several aspects such as economic, military and politics. The CPEC establishment falls under the intention of both countries to gain more advantage in several aspects. The main objective of this journal is to explain non-economic and also economic interests behind China and Pakistan relations especially China’s strategic and geopolitical interests. This journal also analyzes Chinese counter-measures against Indian influence in the Indian Ocean. The conclusion of this research shows that China gain more benefits from CPEC especially after the deployment of China’s Navy into the Gwadar Sea Port.